PERKUATAN (STRENGTHENING) STRUKTUR KOLOM DENGAN METODA PENAMBAHAN TULANGAN - Christiawan, Ignatius (Gema Teknologi, 2011)
Ignatius Chistiawan, in this paper explain that in the management of buildings, frequent damage to buildings due to the increasing load beyond the load plan. Safety of building users to the dangers of building collapse is the main priority. The addition of load beyond the load on the building plans because of changes in building functions often lead to the collapse of the building. The addition of load beyond the load on the building plans because of changes in building functions often lead to the collapse of buildings. Structural strength evaluation to the condition of existing building is required and when it is necessary to give reinforcement to the plate, beams and columns before adding a new load. additional reinforcement is one way of strengthening the column. Research was focused on performance evaluation of structure on existing condition relate at regulation of the Procedure of Concrete Structure Calculation for the SNI 2847-2002. From some previous research, the basics of analysis and design of flexible and practical calculation examples retrofitting columns with the addition of reinforcement can be concluded that this method is easy and practically implemented and can improve the flexural strength of reinforced concrete columns. Keywords : load addition, evaluation, strength, safety.